Transient numerical investigation of a large-scale hydro-pneumatic suspension considering variations in check valve parameters and operational conditions. Issue 4 (8th July 2019) - Zhang, Sha; Gu, Zhengqi; Wu, Wenguang; Zheng, Ledian; Liu, Jun; Yin, Shanbin
Abstract : Purpose: The purpose of this paper is to develop a numerical model used for calculating the nonlinearities of large-scale hydro-pneumatic suspension (HPS) and investigating the effects of variations in flow path and operational parameter on suspension damping response. Design/methodology/approach: To parameterization nonlinearities of the suspension, the author developed a two-phase flow model of a large-scale HPS based on computational fluid dynamics and volume of fluid method. Considerable effort was made to verify the nonlinearities by field measurements carried out on an off-highway mining dump truck. The investigation of effects of variations in flow path and operational parameter on damping characteristics highlights the necessity of the numerical simulation. Findings: The two-phase flow model can represent the gas-oil interaction and simulate the suspension operational movement conveniently. Transient numerical simulation results can be used to model the nonlinearities of large-scale HPS accurately. A new phenomenon was discovered that the pressure in rebound chamber presents reduction trend during compression stroke in special cases. It has never been reported before. Originality/value: Developed a two-phase flow model of a large-scale HPS, which can manage the gas-oil interaction and capture the complex flow field structure in it. The paper is the first study to model the nonlinearities of a large-scale HPS used in off-highway mining dump truck through transient numerical simulation. Compared with previous researches, such a research not only gives new insight and thorough understanding into the suspension internal fluid structure but also can give good guiding opinions to the optimal design of HPS.